2019
DOI: 10.1152/ajpendo.00288.2018
|View full text |Cite
|
Sign up to set email alerts
|

Phospholamban deficiency does not alter skeletal muscle SERCA pumping efficiency or predispose mice to diet-induced obesity

Abstract: The sarco(endo)plasmic reticulum Ca2+-ATPase (SERCA) pump is a major contributor to skeletal muscle Ca2+ homeostasis and metabolic rate. SERCA activity can become adaptively uncoupled by its regulator sarcolipin (SLN) to increase the energy demand of Ca2+ pumping, preventing excessive obesity and glucose intolerance in mice. Several other SERCA regulators bear structural and functional resemblance to SLN, including phospholamban (PLN). Here, we sought to examine whether endogenous levels of skeletal muscle PLN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
1
15
1
Order By: Relevance
“…It should be noted that our apparent coupling ratio values calculated in this study (with or without NNAT) are far below the expected 2 Ca 2+ ions transported per ATP hydrolyzed. Though our values are consistent with recently published reports measuring SERCA coupling ratio in the presence and absence of a Ca 2+ gradient [15,17,48,57], earlier studies have shown coupling ratio values closer to 2 (Ca 2+ : ATP) [12,13,16,58]. Cornelius and Møller [12] measured the electrogenicity of SERCA‐mediated Ca 2+ transport in reconstituted proteoliposomes and found that ˜ 4 electrostatic charges were transferred across the membrane for every ATP hydrolyzed, corresponding to a coupling ratio of 1.8 ± 0.4 Ca 2+ per ATP split.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It should be noted that our apparent coupling ratio values calculated in this study (with or without NNAT) are far below the expected 2 Ca 2+ ions transported per ATP hydrolyzed. Though our values are consistent with recently published reports measuring SERCA coupling ratio in the presence and absence of a Ca 2+ gradient [15,17,48,57], earlier studies have shown coupling ratio values closer to 2 (Ca 2+ : ATP) [12,13,16,58]. Cornelius and Møller [12] measured the electrogenicity of SERCA‐mediated Ca 2+ transport in reconstituted proteoliposomes and found that ˜ 4 electrostatic charges were transferred across the membrane for every ATP hydrolyzed, corresponding to a coupling ratio of 1.8 ± 0.4 Ca 2+ per ATP split.…”
Section: Resultssupporting
confidence: 91%
“…Orlowski and Champeil [13] also found that two Ca 2+ ions were transported into the SR lumen after ATP hydrolysis, and that the dissociation of these two Ca 2+ ions from SERCA and into the lumen occurred at a similar rate. Thus, the apparent coupling ratio values presented in this study, and those from recent reports [15,17,48,57] are likely underestimating the true coupling ratio. The reasons for this discrepancy remain unknown.…”
Section: Resultscontrasting
confidence: 76%
“…The left ventricle was used to examine SERCA protection by PLN for the same reason. We suggest in mice, SLN and PLN would be expected to protect SERCA in slow-twitch muscle where they are normally expressed [62][63][64][65] but not in fast-twitch muscle where they are not normally expressed [64,66]. However, in humans, SLN would be expected to provide greater SERCA protection in fast-twitch muscle, which contains relatively high levels of SLN and relatively low levels of PLN protein, whereas PLN would be expected to provide greater SERCA protection in slow-twitch muscle, which contains relatively high levels of PLN and relatively low or undetectable levels of SLN protein [65].…”
Section: Discussionmentioning
confidence: 87%
“…Similar to T1DM, RyR protein content was decreased in db/db mice (Eshima et al, 2019). By contrast, no differences in the RyR protein content between HFD-induced obese mice and mice fed a normal diet (Eshima et al, 2017b;Gamu et al, 2019). On the other hand, oxidation of RyR has been implicated in Ca 2+ leakage from the SR that causes muscle weakness in aged mice (Andersson et al, 2011).…”
Section: Ryanodine Receptormentioning
confidence: 99%
“…• Northern blotting and WB Zemel et al, 1990;Agil et al, 2015Jain et al, 2014Bach et al, 2003 HFD rats Jaque -Fernandez et al, 2020Bal et al, 2012Ciapaite et al, 2015Eshima et al, 2017aGamu et al, 2019Funai et al, 2016Jheng et al, 2012Liu et al, 2014;Li et al, 2018Taddeo et al, 2014Tubbs et al, 2018DHPR, Dihydropyridine Receptor;HFD, High-Fat The MCUs are regulated by mitochondrial Ca 2+ uptake 1 (MICU1), MICU2, and mitochondrial calcium uniporter regulator 1 (MCUR1), which binds Ca 2+ with high affinity and promotes uptake by mitochondria (Mammucari et al, 2016). Overexpressing MCU increases the mitochondrial size and causes muscle hypertrophy (Barclay et al, 2007;Mammucari et al, 2015).…”
Section: Rodentmentioning
confidence: 99%